Standardisation of RTS beverage from reconstituted cashew apple-based blended juice powder along with Sugandi - Rao, K. Umamaheswara; Kumar, B. Prasanna; Swami, D.V.; Sunnetha, B. Salomi; Krishna, K. Uma; Smith, D.D. (Journal of Plantation Crops, 2021)
Cashew has commercial value for its nut and peduncle (false fruit), known as cashew apple. Requirements of consumers considering convenience, food safety, health benefits and sensory quality have increased demand for fruit juices, but most consumers don’t get time for the ready to use products. Instant juice powders can meet consumer requirements being cheap to transport and with prolonged shelf life. Then the blended juice was mixed with maltodextrin @15 per cent, i.e., 15 g for 100 mL of blended juice by proper homogenisation. The roots of the sugandi (Swallow root - Decalepsis hamiltonii) were collected, cleaned thoroughly and discarded the central white portion of the roots. Among the blended juice treatment combinations, the highest pH of 3.45 was recorded in B3 (75% cashew apple juice + 25% pineapple juice powder at 150°C inlet temperature with a flow rate of 10 mL min-1). The ready-to-serve (RTS) beverage, along with sugandi stored under refrigerated condition, were free from microbial proliferation till the end of the storage period (60th day of storage), indicating its fitness for consumption with maximum flavour, taste and overall acceptability.